Studi Autopsi Psikologis: Identifikasi Faktor Psikologis Penyebab Bunuh Diri di Beberapa Negara di Asia - Ramadhani, Rr Zahra Maghfira; Probowati, Yusti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Suicide remains a critical public health issue in many Asian countries, with increasing rates observed across diverse cultural and social contexts. Understanding the psychological factors underlying suicide is essential for developing effective prevention strategies. This study aimed to identify the psychological factors contributing to suicide in several Asian countries and to explore potential patterns through a literature-based psychological autopsy approach. The data analyzed consisted of psychological autopsy studies on suicide cases from South Korea, Japan, Nepal, Bangladesh, China, and Indonesia. A narrative synthesis was conducted on selected full-text articles published within the last ten years that met the inclusion criteria. The findings revealed that the dominant psychological factors varied across countries. In South Korea, China, and Indonesia, mental health problems particularly mood disorders were identified as the most prominent psychological factors associated with suicide. In Japan, sleep disorders emerged as the most dominant psychological factor. In Bangladesh, negative life experiences were found to be the primary psychological contributors, while in Nepal, exposure to physical violence and witnessing or being aware of suicidal behavior among close individuals played a significant role. These findings indicate that suicide in Asian countries is shaped by a complex interaction of psychological vulnerabilities and sociocultural stressors. Despite these variations, mental health problems remain a recurring core factor across multiple contexts. This study highlights the importance of culturally sensitive suicide prevention strategies that consider country-specific psychological risk factors. The results provide valuable insights for mental health professionals, policymakers, and researchers in designing evidence-based interventions tailored to the sociocultural characteristics of different Asian societies.